Internalisasi Nilai-Nilai Pendidikan Agama Islam dalam Pembelajaran Pelajaran Al-Islam dan Kemuhammadiyahan di Sekolah Menengah Atas - Badrut Tamam; Robiah Al-Adawiyah; Akhmad Muadin (FENOMENA, 2017)
The educational value of Islam, was the spirit of the character education. However it was a religious education into knowledge, no imprint on the attitudes and behaviors of learners. So that the internalization of Islamic religious education into separate points in education. The problems to be studied this thesis was the implementation and internalization of Islamic education in the learning of subjects Al-Islam and Kemuhammadiyahan in SMA Muhammadiyah 1 Sumenep. Furthermore, the factors that were supporting and inhibiting internalization of such values.This study used descriptive qualitative approach that aimed to understand and described the internalization of Islamic religious education at the sites.The survey results revealed that: First, the educational values of Islamic Religion which consists of faith, worship and morality contained in the subjects of Al-Islam and Kemuhammadiyahan in SMA Muhammadiyah 1 Sumenep implemented well in the aspects of real life. Second, the internalization of such values was done in four ways. The ways that were imitation, habituation, meals (conditioning), sustainability (istiqamah). Third, the factors supporting the process of internalization of Islamic religious education among them was a good environment, parents, curriculum, and teacher. Whereas the inhibiting factors were uncontrolled environment, parents who did not care and problematic, then the limitations of teacher supervision.